Conception to alcohol consumption in young people from the University of Cauca - Molano Tobar, Nancy Janneth; Molano Tobar, Dolly Ximena (Universidad y Salud, 2016)
Objective: To identify the concept against alcohol consumption of young people at the University of Cauca. Materials and methods: An ethnographic qualitative design through observation was performed where 12 university, 6 men and 6 women in 2013 in the city of Popayan Cauca were in-depth guided interviewed with average age of 17.5 years, allowed evaluating sociodemographic and personal aspects about starting and habituation to alcohol. Results: It was identified that alcohol consumption occurs early during the school year specifically, in recent high school levels and is accentuated in college, and extends in the latter the possibility of acquiring other stimulants. Alcohol consumption is due to social pressures, the symbolic value it represents to their peers about maturity, and the feeling of disinhibition generated when confronted for the first time to people of the other sex. Conclusions: Alcohol consumption is a means young people employ for socializing and it represents the gateway to new experiences since it is a legal substance and socially accepted, which is easy to acquire and inexpensive, that allows its high consumption within the youth and university population, a fact that deserves to generate campaigns from universities to prevent this habit.